The answer is 19 all you have to do is add them together
Answer:
Step-by-step explanation:
Answer in the attachment
Answer:
(4, 1)
Step-by-step explanation:
Since the first reflection is over the vertical line x=-3, the y-coordinate remains the same. The x-coordinate of A' will make the point (-3, 4) on the line of reflection be the midpoint between A and A':
(-3, 4) = (A +A')/2
2(-3, 4) -A = A' = (-6-(-7), 8 -4) = (1, 4)
The reflection over the line y=x simply interchanges the two coordinate values:
A'' = (4, 1)